Analysis of anti-osteoporosis function of chlorogenic acid by gene microarray profiling in ovariectomy rat model. Issue 4 (31st August 2018) - Min, Jun; Yuan, Zhen; Zhang, Qiao; Lin, Sijian; Wang, Kai; Luo, Jun
Abstract : The aim of the present study was to clarify the effect of chlorogenic acid (CGA) on estrogen deficiency-induced osteoporosis based on micro-computed tomography (micro-CT) and potential mechanism of gene regulation via microarray profiling. Eighteen female Sprague–Dawley rats were divided randomly into sham-operated group, ovariectomy (OVX) plus saline vehicle group, and OVX plus CGA treatment group (CGA at 45 mg/kg/day). The loss of bone mass of the femoral metaphysis was evaluated by micro-CT to represent. Gene expression profiling was analyzed for bone marrow mesenchymal stem cells (BMSCs) of OVX and OVXT groups. Bioinformatics analysis was used to find the potential pathways regulated by CGA. OVX-induced osteoporosis could decrease femur bone mineral density (BMD), bone volume/tissue volume (BV/TV), trabecula number (Tb.N), and trabecular thickness (Tb.Th) and increased the trabecular separation (Tb.Sp) and structure model index (SMI) in the rats. Gene microarray profiling showed 121 differentially expressed genes in collected BMSCs between OVX and OVXT groups were identified with a threshold of a two-fold change and P <0.05. Kyoto Encyclopedia of Genes and Genomes (KEGG) was used to analyze the potential mechanism of CGA and we observed that many mitogen-activated protein kinase (MAPK) pathway associtated genes were altered, suggesting this pathway may play an important role. CGA improved bone quality by modifying the BMD and trabecular microarchitecture. Differential expression genes were screened by gene microarray profile and the results suggested MAPK pathway might participate in the process of OVX-induced bone remodeling.